Dissolved air flotation as a potential wastewater treatment process in the removal of nickel laterite particles from a dilute suspension - Tungpalan, Djoan Kate T. (2011.)
This study aimed to determine the potential of using Dissolved Air Flotation (DAF) in treating wastewater with extremely small inorganic contaminants in very dilute aqueous suspension. A DAF setup was designed to investigate operating parameters that respond to the removal of very low concentrations of nickel laterite particles from a bulk of wastewater. The setup was composed of a saturator where air was dissolved in water and a flotation cell where the saturated water released to produce microbubbles forming a froth layer. the attachment of nickel laterite particles with microbubbles happened in the froth layer and the scraping of this loaded froth layer resulted in the separation of nickel laterite particles from the bulk wastewater. The parameters investigated were saturation pressure, saturation time, volume ratio of water to air, and various dosages of frothers and flocculants. Photographic images of froth formation showed a thicker and more stable layer when frother is added at 50 psi saturation pressure, two minutes saturation time and two liters of water. Operating at these parameters, the efficiency of DAF in removing nickel laterite particles was determined by investigating the effects of different types and doses of frothers, particles sizes of the nickel laterite, concentration of the nickel laterite, and the addition of different concentrations of flocculants. Total Suspended Solids (TSS) method was used to monitor the treatment in terms of concentration of nickel laterite particles removed. A simulated wastewater containing nickel laterite with particles size less than 37 microns was also prepared. Six different frothers were used, namely, Nasfroth 240, Nasfroth 250, Nasfroth 301, Dowfroth 250, Pine Oil and Ethanol. Their dosages were varied from 0.005 to 0.1% by volume. It was found out that a maximum frother dosage yielded maximum removal. The highest removal was 37.65% at 0.034% using Nasfroth 301, from a 1.29% removal in the absence of a frother. To identify the effect of particle size, the particle size range was changed to 80% minus 74 plus 37 microns and 20% less than 37 microns. Results showed lower yield of 7.06% removal for coaser particles which only proves that DAF is more efficient in the removal of finer particle sizes. It was also observed that a maximum nickel laterite concentration yielded the highest removal of nickel laterite. This concentration was achieved at 87 mg/L and further increase in solids concentration no longer increased the removal. On the other hand, the addition of 60% by weight flocculants showed significant improvement in the performance of DAF - yielding a 62.96% removal. However, further addition of flocculants resulted in the decrease in the removal of nickel laterite psrticles from the wastewater.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Water -- Purification -- Dissolved air flotation; Sewage -- Purification -- Flotation; Nickel ores; Laterite